Aliskiren Improves Ischemia- and Oxygen Glucose Deprivation-Induced Cardiac Injury through Activation of Autophagy and AMP-Activated Protein Kinase - Chiang, Ming-Hsien; Liang, Chan-Jung; Liu, Chen-Wei; Pan, Bo-Jhih; Chen, Wen-Ping; Yang, Yi-Fan; Lee, I-Ta; Tsai, Jaw-Shiun; Lee, Chiang-Wen; Chen, Yuh-Lien (Frontiers in Pharmacology, 2017)
Aliskiren is a direct renin inhibitor that has been effective in anti-hypertension. We investigated whether aliskiren could improve the ischemia-induced cardiac injury and whether the autophagy was involved in this effect. A myocardial infarction (MI) model was created by the ligation of the left anterior coronary artery in C57J/BL6 mice. They were treated for 1, 3, 7, and 14 days with vehicle or aliskiren (25 mg/kg/day via subcutaneous injection). In vivo, the MI mice exhibited worse cardiac function by echocardiographic assessment and showed larger myocardial scarring by light microscopy, whereas aliskiren treatment reversed these effects, which were also associated with the changes in caspase-3 and Bcl-2 expression as well as in the number of apoptotic cells. Aliskiren increased autophagy, as demonstrated by LC3B-II expression and transmission electron microscopy. Furthermore, H9c2 cardiomyocytes were employed as an in vitro model to examine the effects of aliskiren on apoptosis and autophagy under oxygen glucose deprivation (OGD)-induced injury. Aliskiren significantly increased cell viability in a dose-dependent manner. The beneficial effects of aliskiren were associated with decreased apoptosis and mitochondrial membrane potential as well as increased autophagy via increased autophagosome formation. We also found that aliskiren-induced cardiomyocyte survival occurred via AMP-activated protein kinase (AMPK)-dependent autophagy. Taken together, these results indicated that aliskiren increased cardiomyocyte survival through increased autophagosomal formation and decreased apoptosis and necrosis via modulating AMPK expression. AMPK-dependent autophagy may represent a novel mechanism for aliskiren in ischemic cardiac disease therapy.